INCARCERATED FEMORAL HERNIA PRESENTING AS CHRONIC NONSPECIFIC GROIN PAIN IN A YOUNG MALE - A VERY RARE CASE REPORT WITH LITERATURE REVIEW - Islam, Shariful; Naidoo, Vijaya; Ramnarine, Malini; Bheem, Vinoo; Naraynsingh, Vijay (International Journal of Research -GRANTHAALAYAH, 2018)
Femoral hernia is uncommon of all groin hernias. It is commonly seen in elderly multiparous female patient. However, presentation of femoral hernia in a male patient is very rare. Only few cases of femoral hernia are reported in male patients in the English literature. Presentation of this hernia can be varied from asymptomatic to incarcerated groin lump. Diagnosis can often be very difficult on clinical examination alone especially in obese male patients. CT imaging should be used as an adjunct in making the right diagnosis when unsure. We present the case of a 42 year male COPD (Chronic Obstructive Pulmonary Disease) patient who visited several general practitioners for his chronic right groin pain with no relief. He was subsequently admitted to the General Hospital and a CT scan of the abdomen and pelvis was done which revealed a right femoral hernia. Emergency surgical repaired was performed. Literature search was performed and management of these hernias is highlighted.